THE EFFECT OF THE USE OF UEU E-LEARNING MEDIA ON THE SKILLS WRITING SKILLS IN THE FOUR SEMESTER FOR THE EYE SKILLS OF INDONESIAN LANGUAGE SKILLS AT ESA UNGGUL UNIVERSITY - Firman Syah, Ezik (IJLECR (International Journal of Language Education and Cultural Review), 2020)
The problem that occurs is related to the large number of lecturers using the e-learning application UEU to teach in the environment of the University of America Superior as a medium for distance learning. The purpose of this study was to determine the effect of the use of UEU e-learning media on short story writing skills in the fourth semester for Indonesian language skills courses at Esa Unggul University. This study uses an experimental method with the research design used is the Pre-Experimental Design type (One Group Pretest Posttest Design) because this study uses one class group as a sample, and there is no control class as a comparison. The data used are the results of students’ short story writing skills when using e-learning learning media. The instruments of this study used the normality test, homogeneity test, correlation test, regression test, correlation test, coefficient of determination, and hypothesis testing. The results of the study of the influence of the use of UEU e-learning media on short story writing skills in the fourth semester for Indonesian language courses at the University of Esa Unggul showed acceptable if the count ≤ ttabel or sig> α value. This is when the pretest test got 7, 248 when teaching short stories using face-to-face comparisons, but after using the e-learning application UEU experienced a significant change of 23,200 in making short stories. Keywords: Media e-learning, short story writing.